ANALYSIS OF AFFECTING FACTORS WHICH INFLUENCE THE PURCHASE OF ORGANIC VEGETABLES IN MEDAN CITY - Yudha Andriansyah Putra (JASc (Journal of Agribusiness Sciences), 2017)
Organic vegetables as one of the products produced from agriculture is environmentally friendly and more closer to the concept of nature, so as to provide better quality assurance compared with ordinary vegetables. This raises its own appeal to certain class consumers who then change their vegetable consumption patterns from inorganically cultivated vegetables to organic vegetables, so that the attractiveness and popularity of inorganically cultivated vegetables is reduced for certain class consumers. Therefore it is necessary to examine the factors - factors that affect the purchase of organic vegetables, especially in the city of Medan. The purpose of this research is to analyze the influence of price ratio between organic and non organic vegetables, advertisement, packaging, family income, education level of respondent, composition of respondent's family member, respondent's age to the purchase of organic vegetables in Medan city. The data used in this study are primary data (directly from consumers who buy organic vegetables) and secondary data (Data from agencies that support this research). The analytical method used is with Multiple Linear Regression using SPSS 17 software.The result of the analysis shows that there are 4 variables which have significant influence, that is the variable ratio of organic vegetable price with non organic, family income, and age of respondent, advertisement, and there are 3 variables which have no significant effect, that is packaging, respondent education level, family member composition.Keyword : Organic Vegetable, price ratio, income, age, advertising